Analisis Faktor-Faktor Yang Membentuk Tingkat Kesetiaan Pelanggan dalam Industri Jasa Kelistrikan di Daerah Istimewa Yogyakarta, Provinsi Jawa Barat, Jawa Tengah, dan Aceh - Risdwiyanto, Andriya; Sjoraida, Diah Fatma; Ahmada, Naufal Haidar; Andriyani, Devi (Jurnal EMT KITA, 2023)
This study investigates the factors that shape customer loyalty in the electricity service sector in Yogyakarta Special Region, West Java, Central Java, and Aceh provinces. The main objective is to analyze the influence of service quality, customer value, and company image on customer loyalty. This study was conducted among several electric service companies in the mentioned areas, with 150 respondents. The overall analysis results show that all research variables have a significant impact on the level of customer loyalty to products in the electrical service sector. This is supported by the Fcount value exceeding FTable at the 5% significance level. Additionally, the T-test results partially confirm that service, customer value, and company image significantly influence customer loyalty to electric service companies. Company image seems to be the most decisive factor in customer loyalty. Therefore, it is important for stakeholders in the electrical services sector in the region to maintain and improve their corporate image with the aim of building customer loyalty.